2017
DOI: 10.1002/2017gc006821
|View full text |Cite
|
Sign up to set email alerts
|

The dynamical control of subduction parameters on surface topography

Abstract: The long‐wavelength surface deflection of Earth's outermost rocky shell is mainly controlled by large‐scale dynamic processes like isostasy or mantle flow. The largest topographic amplitudes are therefore observed at plate boundaries due to the presence of large thermal heterogeneities and strong tectonic forces. Distinct vertical surface deflections are particularly apparent at convergent plate boundaries mostly due to the convergence and asymmetric sinking of the plates. Having a mantle convection model with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 91 publications
(169 reference statements)
5
46
3
Order By: Relevance
“…Accordingly, the arc‐trench distances in present‐day subduction zones lie mostly within the range 150–300 km (e.g., Syracuse & Abers, ). Other profound differences exist between the results reported by Crameri et al () and ours, which may be caused by the different assumptions on rheology. They might also highlight the effect of the OP velocity.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…Accordingly, the arc‐trench distances in present‐day subduction zones lie mostly within the range 150–300 km (e.g., Syracuse & Abers, ). Other profound differences exist between the results reported by Crameri et al () and ours, which may be caused by the different assumptions on rheology. They might also highlight the effect of the OP velocity.…”
Section: Discussioncontrasting
confidence: 84%
“…Their models, limited to the slab‐sinking phase, consistently show the development of a bulge and a relatively large and deep depression. Unlike other studies, Crameri et al () suggested that the bulge corresponds to the island arc and the depression to a back‐arc depression. Although no details are given by the authors on the horizontal distance between the trench and the bulge that their models produce, we can roughly estimate it to be about 100 km.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations